Productivity of meadow clover on sod-podzolic soil with various content of mobile phosphorus and degree of acidity - I. V. Lyskova; T. V. Lyskova; F. A. Popov (Аграрная наука Евро-Северо-Востока, 2019)
The influence of after-effect of mineral fertilizers and lime on productivity of meadow clover 'Dymkovsky' with regard to the content of mobile phosphorus in the soil have been studied in a long stationary trial (established in 1971) on sod-podzolic soil developed on clay loam mantle in the Kirov region. The study was conducted in 2008-2018 on soil backgrounds with various acidity and mobile phosphorus sufficiency: without lime application (рН 3.68, Al 11-17 mg/100g of soil, P2O5 142-291 mg/kg of soil) and with lime application (рН 5.5, Al was not revealed, P2O5 120-232 mg/kg). In variants without application of phosphoric fertilizers the mobile phosphorus sufficiency was 77-84 mg/kg against acid background, and 66-89 mg/kg against limed background. The average yield of clover green mass in 2012 was 17.24 t/ha against acid background and 30.77 t/ha against limed background; the increase due to lime application was 78.4%, in 2018 – 13.0 t/ha, 28.3 t/ha, 118%, respectively. Reliable correlation links have been revealed between the degree of soil acidity (рН and Hh) and productivity of clover green mass, r = 0.76 and r = -0.79, respectively. The effect of the content of mobile phosphorus in the soil on clover productivity was insignificant. Weather conditions during the research influenced the content of crude protein in clover dry mass: in 2012 this indicator varied from 11.92 to 12.74% on the average, in 2018 ‒ from 17.47 to 19.88% against acid and limed background, respectively.